Voices of Malaysian Indian Writers Writing in English - Shangeetha R.K. (Kajian Malaysia, 2020)
This article brings together a compilation of poems, short stories and novels written by Malaysian Indian writers from 1940 to 2018. These verse and prose forms collected here were all written in English within the last 80 years. In fact, in the contemporary Malaysian literary scene, the number of works by Malaysian Indian writers writing in English, has increased compared to the previous volumes which were primarily dominated by writers such as Cecil Rajendra, K.S. Maniam and M. Shanmughalingam. It is interesting to note that the interest of writing poetry and prose among the younger Malaysian Indian writers is on the rise with publications from younger poets and writers such as Paul GnanaSelvam and Cheryl Ann Fernando. In Malaysia, poetry and prose written by Malaysian Indian writers in English is diversifying with many promising new talents. Departing from the Malaysian Indian diaspora, the emerging themes of these lesser-known writers are more liberal. As such, the main aim of this article is to map out the cartography of Malaysian Indian works in these three genres; poem, short story and novel, and identify the main thematic concerns in the writings.